A study of the effects of swirl and tumble ratios on engine performance in motorbike - Ly, Vinh Dat; Le , Thanh Quang; Do , Tan Thich (Journal of Technical Education Science, 2019)
Nowadays, motorbike is a main and popular transport in Asia countries that includes Vietnam. Manifold intake system in motorbike has a simple structure. Hence it reduces engine performance and increases fuel consumption in a motorbike. The paper studies the improving of intake system in 125cc motorbike engine, this improves air-fuel mixture that increases engine performance. The study uses Ansys software to simulate the improving of intake system via tumble and swirl ratios at different cases. Besides, a model is also built by Matlab/Simulink that examines the effects of swirl and tumble ratios on engine performance and fuel consumption in an engine at various engine speeds. The simulation results show that the modified intake system (with 300 angle) has an optimal tumble and swirl ratios. Additionally, power and torque in engine has high value with the modified intake system (with 300 angles). Whereas, the fuel consumption reduces comparing to the other cases.